2010
DOI: 10.1111/j.1708-8305.2010.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well‐Being Factors Associated With International Business Travel

Abstract: This study demonstrated both positive and negative associations on the health risks and well-being of a large sample of US-based international business travelers from an US multinational company. This study identifies targeted areas for pretrip screening and counseling to proactively address potential negative effects of travel and may assist in the design of corporate travel health and employee assistance programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 6 publications
3
52
2
Order By: Relevance
“…Time constraints, lack of leisure time as well as health issues are widely reported consequences among international business travelers which, once more confirms existing studies (e.g. Burkholder, 2010;Welch & Worm, 2006;Harris, 2002;DeFrank, Konopaske, & Ivancevich, 2000). But while stressors related to travelling itself are perceived with different intensity by female and male travelers -women report higher stress levels before and after a trip, whereas men show equal ones (see also Westman, Etzion, & Gattenio, 2008) -consequences such as lack of time or missing time for leisure or social contacts are much more stressed by women in our sample.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Time constraints, lack of leisure time as well as health issues are widely reported consequences among international business travelers which, once more confirms existing studies (e.g. Burkholder, 2010;Welch & Worm, 2006;Harris, 2002;DeFrank, Konopaske, & Ivancevich, 2000). But while stressors related to travelling itself are perceived with different intensity by female and male travelers -women report higher stress levels before and after a trip, whereas men show equal ones (see also Westman, Etzion, & Gattenio, 2008) -consequences such as lack of time or missing time for leisure or social contacts are much more stressed by women in our sample.…”
Section: Discussionsupporting
confidence: 88%
“…Especially the lack of sleep and irregular wake-and-sleep times are a burden for the body as well. Burkholder, Joines, Cunningham-Hill, and Xu (2010) reports about problems in physical coordination and reaction time, physical and mental performance or reduced productivity which might in the long run lead to chronic diseases such as diabetes or depression. Jet-lag, for example, is disturbing the rhythm and might have an impact on cognitive abilities (Burkholder et al, 2010).…”
Section: Health Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…(Boukas & Ziakas, 2016) Cyprus "The paper explores how Cyprus can increase its competitiveness, sustaining its magnitude and attractive attributes, and ensuring residents' well-being" (p. 44). (Burkholder et al, 2010) US "The objective of this study was to determine if the frequency and duration of international business travel is liked to travelers' health and wellbeing" (p. 329).…”
Section: Resultsmentioning
confidence: 99%
“…Pratt et al (2016) found, in Fidgi, that one village that is dependent on tourism has lower levels of happiness when compared to another village where tourism is almost non-existent. Burkholder et al (2010) concluded that there is a positive but also a negative relationship between business travelers' health risks and wellbeing. Mäkelä and Kinnunen (2016) examining international business travel and psychological wellbeing found that workload and work pressure are predictive of exhaustion.…”
Section: Reference Location Paper Aim(s)mentioning
confidence: 99%